Comportamiento epidemiológico de las enfermedades Newcastle y Micoplasmosis en aves de traspatio de la provincia de Cotopaxi - Coronel Acuña, Mayra Cleofe (2024)
The objective of this research work is to evaluate the epidemiological behavior of Newcastle and Mycoplasmosis diseases in backyard poultry of parishes that make up the Cotopaxi province. The methodology applied was quantitative through the indirect ELISA technique. A simple random probabilistic sampling was applied, in which 384 birds were divided into groups of 38 parishes (12 samples per each). These samples were transported to the laboratory to extract the blood serum and obtain the results that determine the prevalence of Newcastle and Mycoplasmosis diseases in Cotopaxi province. The results revealed that the highest prevalence of Newcastle disease (over 50%) was found in the parishes of Pujili, El Tingo with 83.33%, Pilalo (66.67%), Guanjage (58.33%); Salache with 58.33%; and Bethlemitas with 50% in Latacunga. On the other hand, in Mycoplasma, the prevalence of over 50% was found in parishes of Guayacan, Pucayacu, Bethlemitas, San Rafael, El Tingo, Pilalo, Zumbahua, Pampas and Pampas 2. With the risk factors for Newcastle disease, it was demonstrated that the breeding destination had a relative risk (RR) of 1.025 for poultry destined for self-consumption. In contrast, the sex had an RR of 0.66, considered negative because male poultry remains less time and in a lower proportion within the productive cycle. When analyzing the RR in roosters/hens vs. chickens/pullets, a value of 2.37 was found for the first group, given that these have a longer productive life. In contrast, the most important risk factor was the economic activity of agriculture. In the case of Mycoplasmosis, about risk factors from the economic point of view and age of birds, agriculture was the highest risk factor in the cantons; Salcedo, Saquisili, and Sigchos were above 90%. Finally, the epidemiological maps indicated that the cantons with the highest prevalence of Newcastle and Mycoplasmosis diseases were Pujili and La Mana, respectively.